2016
DOI: 10.1364/oe.24.013334
|View full text |Cite
|
Sign up to set email alerts
|

Large aperture tunable-focus liquid lens using shape memory alloy spring

Abstract: A tunable-focus large aperture liquid lens is constructed using shape memory alloy (SMA) springs as actuators. The lens mainly consists of a shallow liquid-filled cylindrical cavity bound by a thin compressible annular rim and encapsulated by a flexible circular membrane on the top of the rim and a rigid circular plate at the rim bottom. The lens optical power is adjusted by a controlled compression of the annular rim via actuation of the three shape-memory alloy (SMA) springs. Since the volume of the cavity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, this problem seems solvable in the near future since an aperture of about 20 mm is already enough to achieve more reasonable fnumbers and there are research groups proposing designs for tuneable lenses with diameters of 30 mm and more (e.g. [12,13]). Since the intention behind our experimental setup is a demonstration of the general feasibility of our approach we did not focus on a systems optimization with respect to aberrations etc.…”
Section: Theoretical Considerations and Limitationsmentioning
confidence: 99%
“…However, this problem seems solvable in the near future since an aperture of about 20 mm is already enough to achieve more reasonable fnumbers and there are research groups proposing designs for tuneable lenses with diameters of 30 mm and more (e.g. [12,13]). Since the intention behind our experimental setup is a demonstration of the general feasibility of our approach we did not focus on a systems optimization with respect to aberrations etc.…”
Section: Theoretical Considerations and Limitationsmentioning
confidence: 99%
“…The surface of the liquid is changed by the electric field, which changes the focus. Hasan et al [ 9 ] suggested an accommodating IOL that uses a shape memory alloy spring controlled by electric heat. Vdovin et al [ 10 ] suggested an accommodating IOL that uses a liquid crystal lens deformed by conductive metal that is moved by an electrical field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tunable focus liquid lenses with large optical aperture were also introduced, which provided larger range of tunable power [13][14][15][16]. In order to reduce gravity effects to the performance of liquid lens, one method used an inplane pretention force onto the membrane to take the place of surface tension and another used a nonuniform thickness profile of flexible membrane [17,18].…”
Section: Introductionmentioning
confidence: 99%